Pimpin, Peduli, atau Kehilangan? Transformational Leadership, Ethical Climate, dan Dampak Physical Work Environment Pada Turnover Intention Pekerja Generasi Z - Nabila, Safira Hanun; Salendu, Alice; Nadia, Shofi (Faculty of Psychology, Universitas Surabaya, 2025)
Generation Z, which currently dominates the workforce, has high expectations for work-life balance, material rewards, and supportive physical work environment (PWE). This study explores the influence of transformational leadership (TL), caring ethical climate (CEC), and physical work environment (PWE) on turnover intention (TI) among 317 Generation Z workers across various sectors in Indonesia. Study findings reveal that transformational leadership (TL) directly reduces turnover intention (TI; β = - .70; p < .05), though the mediating effect through caring ethical climate (CEC) is not significant; only evident under low physical work environment (PWE) conditions. Results also show that physical work environment (PWE) plays a significant moderating role (β = - .63; p < .05), strengthening the positive impact of caring ethical climate (CEC) in reducing turnover intention (TI). In other words, a conducive physical work environment (PWE) not only enhances comfort, but also supports the creation of an ethical culture that more effectively lowers turnover intention (TI). This highlights that physical factors in the workplace have a substantial impact, both directly and indirectly, on employee retention. This study underscores the importance of transformational leadership (TL) and the management of physical work environment (PWE) in enhancing the loyalty of Generation Z workers, with results providing strategic insights to improve retention through a holistic approach.